Modern Approaches to Determination of the Biological Activity of Insulin and Its Analogues - T. A. Batuashvili; L. V. Simutenko; P. V. Shadrin; N. P. Neugodova (Регуляторные исследования и экспертиза лекарственных средств, 2019)
The paper considers insulin’s specific action on the patient’s body, types of insulin preparations and insulin analogues which are used for the treatment of diabetes, as well as applicable requirements for these products. It was demonstrated that determination of biological activity is one of the key quality parameters of this type of medicines. The paper summarises the methods used for evaluation of insulin and its analogues, which are based both on the hormone’s general action on the body (in vivo: double crossing, euglycemic clamp, etc.), and on certain aspects of the hormone’s interaction with the body systems (in vitro: receptor-binding assay, phosphorylation, metabolic methods). Due to the appearance of insulin biosimilars on the pharmaceutical market, the article raises the issue that the «Biological potency» parameter tested in animals should be kept as part of the product specification. The analysis of the in vivo and in vitro methods of biological activity determination convincingly demonstrates that animal models can not be replaced with the modern analytical methods based on cell cultures. Consequently, animal models are still necessary, as they allow for an adequate assessment of the quality of insulins in terms of «Biological potency». Taking into account the global trend towards reduction of animal testing, the authors point out the need to develop modern methods, the results of which will be comparable to the results of in vivo determination of the biological activity.